2020
DOI: 10.4314/ijbcs.v14i6.9
|View full text |Cite
|
Sign up to set email alerts
|

Distribution et dégâts associés au thrips de l’oignon, <i>Thrips tabaci</i> L. (Thysanoptera : Thripidae) en fonction de la zone agro-climatique au Burkina Faso

Abstract: L’oignon est le premier légume produit au Burkina Faso. Thrips tabaci constitue son principal insecte ravageur. Ce travail avait pour objectif  d’évaluer la distribution, l’incidence et la sévérité des attaques de T. tabaci sur l’oignon. L’étude a été réalisée dans trois bassins de production  représentatifs de deux zones agroécologiques du Burkina Faso : la zone sahélienne caractérisée par une pluviosité moyenne annuelle inférieure à 600 mm et une température moyenne annuelle de 35 °C ; contre une pluviosité … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
0
0
Order By: Relevance
“…density was significantly higher at sites in the northern production basin compared to sites in the other two production basins. These results confirm those of [8] who also showed that Thrips to 1100 mm with a number of rainy days between 70 and 90 [39]. Yet, according to [15], onion thrips reproduce asexually by parthenogenesis and the rate of reproduction depends on environmental conditions.…”
Section: Discussionsupporting
confidence: 87%
“…density was significantly higher at sites in the northern production basin compared to sites in the other two production basins. These results confirm those of [8] who also showed that Thrips to 1100 mm with a number of rainy days between 70 and 90 [39]. Yet, according to [15], onion thrips reproduce asexually by parthenogenesis and the rate of reproduction depends on environmental conditions.…”
Section: Discussionsupporting
confidence: 87%